English English - Bakhtiar, Erwin; Rochmawati, Dwi Heppy; Susanto, Wigyo; Hendrawan, Gagah Satria (Jurnal Surya, 2025)
ABSTRACT   Introduction: Pulmonary tuberculosis (TB) patients need to have strong effort, desire, and belief in themselves to complete anti-tuberculosis drug (ATD) therapy. A preliminary study conducted on 30 patients observed that there were 12 patients (40%) with a history of incomplete ATD therapy due to non-adherence. This study aims to determine the relationship between self-efficacy and medication adherence in pulmonary TB patients. Methods: This quantitative study used a correlational analysis method with a cross-sectional approach. The collected sample of 60 TB patients used a total sampling technique. Self-efficacy was measured using The General Self-Efficacy Scale (GSE) and adherence to taking ATD was measured using the Morisky Medication Adherence Scales-8 (MMAS-8). The analysis was performed using the Spearman Rank test. Results: A total of 40 patients (66.7%) had moderate level of self-efficacy, and 27 patients (45%) had high level of medication adherence. There was a significant relationship between self-efficacy and adherence to taking ATD with a significance value of <0.001 and a level of closeness of 0.695. Conclusion: The relationship between self-efficacy and adherence to taking ATD is a strong and unidirectional relationship. Families are expected to provide support to improve the self-efficacy of pulmonary TB patients, such as giving confidence to patients to be able to complete TB treatment. Keywords: Adherence, Medication, Self-Efficacy, Tuberculosis